Changes In The Rules For Granting State Aid To Enterprises In The European Union - Stąpniak-Kucharska, Anna (Comparative Economic Research. Central and Eastern Europe, 2014)
The point of departure of EU State aid policy is laid down in the Treaty establishing the European Community (hereinafter the “Treaty”). This Treaty provides that State aid is, in principle, incompatible with the common market. However, the principle of incompatibility does not amount to a full-scale prohibition. In the EU countries state aid is permissible to promote the economic development (of areas where the standard of living is abnormally low or where there is serious underemployment) and to facilitate the development of certain economic activities or certain economic areas (where such aid does not adversely affect trading conditions contrary to the common interest). The provisions of the 2000 Lisbon Strategy and the “Europe 2020” Strategy are also important in determining the directions of state aid in the European Union. According to their assumptions the member countries have been required to: reduce the level of aid relative to GDP; reduce state aid which decreases competition; reorient sectoral aid to horizontal and regional aid; and change the forms of state aid-from passive to active instruments. The purpose of this paper is to present the directions of allocation of state aid in the EU countries during 2000-2011, and answer the question whether the resolutions contained in the Lisbon Strategy have been implemented. The research hypothesis is: have the changes in the size, direction and allocation of state aid taken place in accordance with the resolutions of the Lisbon Strategy.